2019
DOI: 10.1002/cphc.201800792
|View full text |Cite
|
Sign up to set email alerts
|

Niobium Doping in BiVO4: Interplay Between Effective Mass, Stability, and Pressure

Abstract: We have applied density functional theory to study the electronic structure changes caused by Nb incorporation in BiVO4 and the application of external pressure. The overall solubility of Nb in BiVO4 is usually high, and the presence of oxygen vacancies affect the dopability of Nb in BiVO4. Through the analyses of the chemical‐potential landscape, we have determined the single‐phase stability zone of BiVO4 with the Nb doping. The most favorable Nb doping is simultaneous substitutions at both V‐ and Bi‐sites. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Experimentally, the band gap of m-BiVO 4 is around 2.34 eV, and we found that GGA underestimated the band gap by about 0.3 eV. A similar band gap underestimation using GGA was calculated by Saker et al By increasing the U value, we obtained the experimental band gap of m-BiVO 4 at U = 4 eV. HSE06 significantly overestimated the band gap, predicting the band gap value of 3.1 eV, which is similar to the results of Kweon et al, who reported a band gap near 3.5 eV (although with t-BiVO 4 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Experimentally, the band gap of m-BiVO 4 is around 2.34 eV, and we found that GGA underestimated the band gap by about 0.3 eV. A similar band gap underestimation using GGA was calculated by Saker et al By increasing the U value, we obtained the experimental band gap of m-BiVO 4 at U = 4 eV. HSE06 significantly overestimated the band gap, predicting the band gap value of 3.1 eV, which is similar to the results of Kweon et al, who reported a band gap near 3.5 eV (although with t-BiVO 4 ).…”
Section: Resultssupporting
confidence: 90%
“…The equilibrium volume of m-BiVO 4 was obtained by fitting the DFT energies and volume data with the Murnaghan 11 equation of state. The optimized lattice parameters were a = 7.33 A, b = 11.79Å, c = 5.19Å, and β = 135.02 • , in good agreement with other theoreticalresults 17,18.…”
supporting
confidence: 84%
“…The thermal stability of the system with different F-doped concentrations was evaluated using the formation energy (E f ) and it was determined as follows 47,48…”
Section: Computational Detailsmentioning
confidence: 99%
“…Recently, a great deal of effort has been devoted to overcoming short hole diffusion length and rapid charge recombination of BVO photoanodes, through heteroatom doping, oxygen vacancies or structural tuning, heterostructure construction, and loading of oxygen evolution cocatalysts (OECs) . Loading OEC on a BVO surface is regarded as a feasible approach to optimize PEC activity. , However, severe electron–hole recombination at the BVO/OEC interface still limits the PEC water oxidation.…”
Section: Introductionmentioning
confidence: 99%